Optimizing Rice Yield and Heat Stress Resilience Through Nitrogen Top Dressing Before Panicle Emergence - Shafiqullah Aryan; Gulbuddin Gulab; Safiullah Habibi; Tayebullah Zahid; Zabihullah Safi; Nasratullah Habibi; Abdul Basir Mahmoodzada; Mohammad Wasif Amin; Ijaz Ahmad Samsor; Kenji Erie (Nitrogen)
The increased frequency of extreme heat stress events due to climate change is adversely impacting rice yield. Nitrogen (N) is an essential element in the synthesis of chlorophyll in rice, contributing substantially to the achievement of spikelet fertility and addressing the high yields. Two experiments were conducted in Japan and Afghanistan in 2020 and 2022, respectively, utilizing IR64 and Nipponbare (NPB) varieties to elucidate the efficacy of N top-dressing on spikelet fertility and yield of rice under heat stress conditions. In experiment I, the treatments involved were based on N application before panicle emergence in pots, including (1) control (fertilized at the tillering stage), (2) control + N topdressing, (3) heat stress (fertilized at the tillering stage), and (4) heat stress + N topdressing. Experiment II consisted of (1) control (basal dressing at the tillering stage) and (2) control + N topdressing, which was conducted under field conditions. Results showed that N application significantly (p < 0.05) increased SPAD values and spikelet fertility rates in both experiments. A positive correlation (range; r = 0.83–0.98) was observed between enhanced SPAD values and spikelet fertility rates in IR64 and NPB rice varieties under both ambient and heat stress conditions. Moreover, there were notable increases in photosynthetic rate (7.4% to 52.6%) and leaf transpiration. N top dressing significantly (p < 0.05) increased the panicle length, panicle weight, number of secondary branches/panicle, filled grain/panicle, total spikelets/panicle, and yield/plant. However, there was no significant difference in the number of primary branches per panicle and 1000-grain weight. In addition, the number of unfilled grains/panicle decreased from 5.5 to 49.7% with N top dressing in both experiments. Applying N as a top dressing improved the spikelet fertility percentage and other yield components, resulting in a high yield/plant.